Grammaticality judgment test : does it reliably measure English language proficiency? - Tan, Bee Hoon (2014)
Language assessment is an important activity in any language classroom. Out of the various tests or measurements of grammatical competence, one method known as grammaticality judgment is by far the most controversial albeit its advantages in gauging linguistic competence. Research studies on grammatical judgment tests (GJTs) are still getting contradictory research results since its introduction in second language research from the mid-70s (Rimmer, 2006). While productive language tests measure language use of learners (i.e. performance), GJTs are “a standard method of determining whether a construction is well-formed … where subjects make an intuitive pronouncement on the accuracy of form and structure in individual decontextualised sentences” (Rimmer, 2006, p.246). GJTs have been used to gauge linguistic competence of second language learners for more than three decades already, but the results differ. Several studies found GJTs reliable measures of learners’ language competence (e.g. Leong et al., 2012; Rahimy & Moradkhani, 2012), while almost the same number found otherwise (e.g. Ellis, 2005; Tabatabaei & Dehghani, 2011). Therefore, this study aims to contribute empirical evidence to the field by administering a GJT to 100 ESL undergraduates. Comparison is made between the GJT scores and SPM English and MUET results to investigate the correlationship. A strong positive relationship among the three types of English proficiency measurement may indicate the reliability extent of the GJT as a measure of English language competence.